Combining European Society of Cardiology and American College of Cardiology/American Heart Association risk prediction model with polygenic risk scores to refine cardiovascular prevention. (3rd October 2022) - De La Harpe, R; Thorball, C W; Redin, C; Fournier, S; Muller, O; Strambo, D; Michel, P; Vollenweider, P; Marques-Vidal, P; Fellay, J; Vaucher, J
Abstract: Introduction: Polygenic risk scores (PRS) predict the risk of developing atherosclerotic cardiovascular disease (ASCVD). However, their utility in combination with existing clinical risk scores remains uncertain. Purpose: We first validated four different PRS in a Swiss population-based cohort. Second, using the PRS with the best predictive capacity, we assessed its benefit when combined with two clinical risk scores: the Systematic COronary Risk Evaluation 2 (SCORE2) and the Pooled Cohort Equation (PCE). Methods: We used data from a prospective cohort involving 6733 European participants at baseline (2003–2006). The predictive accuracy of the PRS was assessed with discrimination and calibration metrics. For the second aim, subjects with prevalent ASCVD or statin therapy at baseline were excluded. We tested associations between risk prediction models (PRS alone and combined clinical and PRS) and incident ASCVD, using Cox proportional hazard regressions. Net reclassification index (NRI) detected any improvement of ASCVD risk categorisation following the addition of the PRS to clinical risk scores in overall sample and in subgroups (e.g., sex, age, clinical intermediate-risk category) Results: For the first aim, 4215 subjects (53% women; mean age 53.7±10.7), with 357 prevalent ASCVD, were analysed. The PRS developed by Inouye et al. [1], comprising >6 million variants, presented the best predictive capacity (area under the receiver operating characteristic of 0.77) and was used in the following analyses. For the second aim, 3390 subjects (mean follow-up of 12.0±3.3 years), with 188 incident ASCVD, were analysed. Individuals in the top 20% of the PRS distribution had the same magnitude of association with ASCVD as current smokers or diabetic subjects (see Figure 1). Combining the PRS with SCORE2 led to a reclassification of 17.1% (95% CI, 4.7–29.5) of subjects in the intermediate-risk category (see Figure 2). Likewise, adding the PRS to PCE translated into an NRI of 19.2% (95% CI, 4.8–22.4) in the intermediate-risk category (not shown). Conclusion: Using a Swiss population-based cohort, PRS presented good predictive capacities for ASCVD. Combining a PRS with clinical risk scores improved reclassification of risk for ASCVD, especially for subjects in the intermediate-risk category. Introducing PRS in clinical practice may refine cardiovascular prevention for subgroups of patients in whom prevention strategies are uncertain. Funding Acknowledgement: Type of funding sources: None.